2012
DOI: 10.1074/jbc.m112.363382
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epithelial Sodium Channel Trafficking by Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9)

Abstract: Background:The epithelial Na ϩ channel ENaC functions as a pathway for Na ϩ absorption across epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 54 publications
0
59
0
Order By: Relevance
“…(2) In the second example, within the ER/ER-Golgi intermediate compartment of cells, PCSK9 was reported to enhance the degradation of the epithelial Na + channel (ENaC) that is critical for Na + homeostasis and blood pressure control. 74 This observation was intriguing, especially in view of the expression of PCSK9 in the kidney. 12 However, our data revealed that in PCSK9-knockout mice, the basal and angiotensin-II-induced blood pressure rise is not different from wild-type controls, suggesting that EnaC levels are not appreciably increased in the absence of PCSK9, at least in mice (N.G.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) In the second example, within the ER/ER-Golgi intermediate compartment of cells, PCSK9 was reported to enhance the degradation of the epithelial Na + channel (ENaC) that is critical for Na + homeostasis and blood pressure control. 74 This observation was intriguing, especially in view of the expression of PCSK9 in the kidney. 12 However, our data revealed that in PCSK9-knockout mice, the basal and angiotensin-II-induced blood pressure rise is not different from wild-type controls, suggesting that EnaC levels are not appreciably increased in the absence of PCSK9, at least in mice (N.G.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%
“…12 It is also possible that PCSK9 acts locally in some extrahepatic tissues that express this protein (eg, small intestine, pancreas, and kidney), and that its circulating levels would not affect the LDLR in these tissues. The reported possible PCSK9-induced degradation of epithelial Na + channel in kidney cells 74 needs in vivo confirmation because basal blood pressure and angiotensin-II induced rise in blood pressure in mice are not modified by the lack of expression of PCSK9 (N.G. Seidah and T. Reudelhuber, unpublished data, 2014).…”
Section: Adrenals and Kidneysmentioning
confidence: 99%
“…It has been suggested recently that PCSK9 decreases the expression of the amiloride sensitive epithelial Na þ channel (ENaC) at the protein level [7]. As previously described for the regulation of LDLR, the catalytic activity of PCSK9 is not required for reducing ENaC cell surface expression.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies show that PCSK9 induces degradation of epithelial Na( ) channels, which regulate blood pressure by modulating epithelial sodium reabsorption in the collecting ducts 48) . It is unclear whether this cellular observation is related to the regulation of blood pressure, but a large cohort study reported a correlation between blood pr essure and PCSK9 level 43) .…”
Section: Pcsk9 and Several Injurious Agentsmentioning
confidence: 99%